A morphological comparison of two cladopyxidacean dinoflagellates: the extant Micracanthodinium setiferum and the fossil Cladopyxidium saeptum (Dinophyceae, Gonyaulacales). (2nd January 2022) - Mertens, Kenneth Neil; Carbonell-Moore, M. Consuelo; Gardner, Kristina
Abstract: Among dinoflagellates, extant cladopyxidaceans may provide a missing link to better understand the first evolutionary transformations from ancestral configurations toward the more abundant and more derived patterns in Gonyaulacales and Peridiniales. A restudy of the extant, motile-defined Micracanthodinium setiferum using plankton samples from the Indian and Atlantic oceans and the Mediterranean Sea demonstrates that the correct plate formula is Po, Pt, X, 3′ + *4′, 4a, 7′′, 7C, 4S, ?6′′′, 0p, 2′′′′. A ventral pore is found between 1′, 3′ and *4′. A restudy of the extinct, fossil-defined Cladopyxidium saeptum from the upper Paleocene of Delaware (USA), demonstrated the presence of an identical tabulation. A ventral pore (= porichnion) was positioned between *1′ and 7′′. Cladopyxidium is morphologically closer to Micracanthodinium than to Cladopyxis . Since Cladopyxidium has been extinct since the middle Eocene, it is unlikely that Micracanthodinium and Cladopyxidium have a direct biological link; the close morphological similarity between them does, however, suggest an important phylogenetic relationship between them in the evolution of cladopyxidaceans.